Stress Memory in Seagrasses: First Insight Into the Effects of Thermal Priming and the Role of Epigenetic Modifications - Nguyen, Hung Manh; Kim, Mikael; Ralph, Peter J.; Marín-Guirao, Lázaro; Pernice, Mathieu; Procaccini, Gabriele (Frontiers in Plant Science, 2020)
While thermal priming and the relative role of epigenetic modifications have been widely studied in terrestrial plants, their roles remain unexplored in seagrasses so far. Here, we experimentally compared the ability of two different functional types of seagrass species, dominant in the Southern hemisphere, climax species Posidonia australis and pioneer species Zostera muelleri, to acquire thermal-stress memory to better survive successive stressful thermal events. To this end, a two-heatwave experimental design was conducted in a mesocosm setup. Findings across levels of biological organization including the molecular (gene expression), physiological (photosynthetic performances and pigments content) and organismal (growth) levels provided the first evidence of thermal priming in seagrasses. Non-preheated plants suffered a significant reduction in photosynthetic capacity, leaf growth and chlorophyll a content, while preheated plants were able to cope better with the recurrent stressful event. Gene expression results demonstrated significant regulation of methylation-related genes in response to thermal stress, suggesting that epigenetic modifications could play a central role in seagrass thermal stress memory. In addition, we revealed some interspecific differences in thermal responses between the two different functional types of seagrass species. These results provide the first insights into thermal priming and relative epigenetic modifications in seagrasses paving the way for more comprehensive forecasting and management of thermal stress in these marine foundation species in an era of rapid environmental change.